Adaptation to nicotine in the facultative tobacco‐feeding hemipteran Bemisia tabaci. Issue 10 (6th March 2014) - Kliot, Adi; Kontsedalov, Svetlana; Ramsey, John S; Jander, Georg; Ghanim, Murad
Abstract BACKGROUND Plant defensive metabolites such as nicotine can provide barriers to host‐range expansion by generalist herbivores. Nicotine is one of the most abundant and toxic plant secondary metabolites in nature and is defined by high toxicity to plant‐feeding insects. There is significant variation in nicotine tolerance among Bemisia tabaci (tobacco whitefly) isolates. Some nicotine‐tolerant B. tabaci strains can consume 40‐fold higher nicotine levels than susceptible strains, and also show cross‐resistance to neonicotinoid insecticides. In this study, biological and molecular assays were used to investigate the responses of B. tabaci strains that differ in their ability to tolerate dietary nicotine. RESULTS Egg laying and honeydew secretion bioassays as well as gene expression microarrays were used to measure B. tabaci biological parameters and gene transcripts misregulated in response to nicotine in resistant and susceptible strains. The resistant B. tabaci strain laid significantly fewer eggs and excreted more honeydew on a tobacco strain with high levels of nicotine, suggesting a fitness cost effect. The molecular response was drastic in the susceptible strain, while the resistant strain exhibited moderate response. Higher expression of the previously identified CYP6CM1 P450 monooxygenase gene related to the resistance to neonicotinoids, as well as other P450s and metabolic genes, was identified in the resistant and susceptible strains after exposure to nicotine. CONCLUSIONS Nicotine is a very toxic plant natural compound, and its mode of action resembles that of synthetic neonicotinoids. The biological and molecular responses observed in this study suggest that nicotine may play an important role in providing barriers for host‐plant expansion by generalists, and may act as a natural factor that contributes to the development of insect populations resistant to synthetic pesticides. © 2014 Society of Chemical Industry